A portable class of 3‐transistor current references with low‐power sub‐0.5 V operation. (20th December 2017) - Crupi, Felice; De Rose, Raffaele; Paliy, Maksym; Lanuzza, Marco; Perna, Mattia; Iannaccone, Giuseppe
Summary: This work proposes a new class of current references based on only 3 transistors that allows sub‐0.5 V operation. The circuit consists of a 2‐transistor block that generates a proportional‐to‐absolute‐temperature or a complementary‐to‐absolute‐temperature voltage and a load transistor. The idea of a 3T current reference is validated by circuit simulations for different complementary metal‐oxide‐semiconductor technologies and by experimental measurements on a large set of test chips fabricated with a commercial 0.18 μm complementary metal‐oxide‐semiconductor process. As compared to the state‐of‐art competitors, the 3T current reference exhibits competitive performance in terms of temperature coefficient (578 ppm/°C), line sensitivity (3.9%/V), and power consumption (213 nW) and presents a reduction by a factor of 2 to 3 in terms of minimum operating voltage (0.45 V) and an improvement of 1 to 2 orders of magnitude in terms of area occupation (750 μm 2 ). In spite of the extremely reduced silicon area, the fabricated chips exhibit low‐process sensitivity (2.7%). A digital trimming solution to significantly reduce the process sensitivity is also presented and validated by simulations. Abstract : This work proposes a new class of current references based on only 3 transistors that allows sub‐0.5 V operation. The circuit consists of a 2‐transistor block that generates a proportional‐to‐absolute temperature or a complementary‐to‐absolute‐temperature voltage and a load transistor. The idea of a 3T current reference is validated by circuit simulations for different complementary metal oxide semiconductor technologies and by experimental measurements on a large set of test chips fabricated with a commercial 0.18 μm complementary metal oxide semiconductor process. As compared to the state‐of‐art competitors, the 3T current reference exhibits competitive performance in terms of temperature coefficient (578 ppm/°C), line sensitivity (3.9%/V), and power consumption (213 nW) and presents a reduction by a factor of 2 to 3 in terms of minimum operating voltage (0.45 V) and an improvement of 1 to 2 orders of magnitude in terms of area occupation (750 μm 2 ). In spite of the extremely reduced silicon area, the fabricated chips exhibit low‐process sensitivity (2.7%). A digital trimming solution to significantly reduce the process sensitivity is also presented and validated by simulations.